(3MGTjI Ydi ehUd GdWdGH Edi bhGYO GdEYQGH dNGdO GdCRgQjs - (3eLghds ((3GHf eMeO Hf fhQ GdOjf GdQTjOj GdTGaYjs)
(3ChdgG (B:s
(3fGbU GdChd, hjHOC ef bhdg(B: (3hCSCdc GdfXQ Edi hLgc hGdThb Edi dbGFc hGNJda aj GdThb gd jRhd HGdhUGds
(3BNQgG (B:s
(3hjQi ddChGFd GdJbOjeG EP PGc GdbOje cGf LOjOG hSjHbi gPG GdLOjO bOjeG, hGdMeO ddg GdPj gOGfG dgPG heG cfG dfJgOj dhdG Cf gOGfG Gddg hUdi Gddg Ydi SjOfG eMeO hYdi Bd SjOfG eMeO hYdi CUMGH SjOfG eMeOs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs